The CSA Papers: Critical investigations to support climate-smart agriculture development. An effort to analyze, publish, and present previously unreleased data on CSA - Rosenstock, Todd S.; Girvetz, Evan Hartunian; Nowak, Andreea C. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2017)
The CSA Papers aim to generate critical insights into five key areas of CSA based on unpublished scientific information. Contributors of Papers will participate in a writeshop, be provided honoraria, and be eligible for travel grants to showcase their work.